MENGGALI POTENSI LOKAL: PERAN DIGITAL MARKETING DALAM MENIGKATKAN DAYA SAING UMKM DESA KUMEJING - Muhammad Adib Mubarok; Ayu Setia Rahma; Devita Agustina Wulandari; Nadia Maulina Istiqomah; Wahyu Nurkholisah; Lucky Rizki Fadhillah; Qoyyimatur Rosyiqo; Rediva Hani Fathonah; Bodro Sakti Dewo Purnomo; Hera Alana Azharia; Fatiha Cessa Maulida; Erliana Erliana; Fasya Nanda Mulia; Yuria Siska Latifa; Fina Fatu’rahma (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Rural Micro, Small, and Medium Enterprises (UMKM) often face challenges in utilizing digital technology to expand their markets and enhance competitiveness. This study was conducted in Kumejing Village, Wadaslintang District, Wonosobo Regency, aiming to analyze the effectiveness of the program “Exploring Local Potential: The Role of Digital Marketing in Enhancing the Competitiveness of UMKM in Kumejing Village.” The research employed a qualitative method through observation, interviews, and documentation. The program was implemented by Community Service Program (KPM) students in collaboration with the village government and local UMKM through business data collection, program socialization, and digital platform mentoring. The findings indicate that the application of digital marketing, particularly through Instagram, Linktree, and Google Maps, successfully increased product visibility, expanded market reach, and strengthened brand identity. Moreover, the program equipped MSME actors with sustainable digital skills, enabling them to remain competitive in the modern era.